Molecular tools for studying the major malaria vector Anopheles funestus: improving the utility of the genome using a comparative poly(A) and Ribo-Zero RNAseq analysis. (December 2015) - Weedall, Gareth; Irving, Helen; Hughes, Margaret; Wondji, Charles
Abstract Background Next-generation sequencing (NGS) offers great opportunities for studying the biology of insect vectors of disease. Prerequisites for successful analyses include high quality annotated genome assemblies and that techniques designed for use with model organisms be tested and optimised for use with these insects. We aimed to test and improve genomic tools for studying the major malaria vectorAnopheles funestus . Results To guide future RNAseq transcriptomic studies ofAn. funestus, we compared two methods for enrichment of non-ribosomal RNA for analysis: enrichment of polyadenylated RNA and ribosomal RNA depletion using a kit designed to deplete human/rat/mouse rRNA. We found large differences between the two methods in the resulting transcriptomes, some of which is due to differential representation of polyadenylated and non-polyadenylated transcripts. We used the RNAseq data for validation and targeted manual editing of the draftAn. funestus genome annotation, validating 62 % of annotated introns, manually improving the annotation of seven gene families involved in the detoxification of xenobiotics and integrated two published transcriptomic datasets with the recently published genome assembly. Conclusions The mRNA enrichment method makes a substantial, replicable difference to the transcriptome composition, at least partly due to the representation of non-polyadenylated transcripts in the final transcriptome. Therefore, great care should be taken in comparing gene expression data among studies. Ribosomal RNA depletion of total RNA using a kit designed to deplete human/rat/mouse rRNA works in mosquitoes and, we argue, results in a truer representation of the transcriptome than poly(A) selection. TheAn. funestus genome annotation can be considerably improved with the help of these new RNAseq data and further guided manual gene editing efforts will be of great benefit to theAnopheles research community for studies of this insect's genome and transcriptome.